The effect of local variation in malaria transmission on the prevalence of sulfadoxine–pyrimethamine resistant haplotypes and selective sweep characteristics in Malawi. (December 2015) - Artimovich, Elena; Kapito-Tembo, Atupele; Pensulo, Paul; Nyirenda, Osward; Brown, Sarah; Joshi, Sudhaunshu; Taylor, Terrie; Mathanga, Don; Escalante, Ananias; Laufer, Miriam; Takala-Harrison, Shannon
Abstract Background Persistence of sulfadoxine–pyrimethamine (SP) resistance has been described in an urban setting in Malawi where malaria transmission is relatively low. Higher malaria transmission is associated with greater genetic diversity and more frequent genetic recombination, which could lead to a more rapid re-emergence of SP-sensitive parasites, as well as more rapid degradation of selective sweeps. In this study, the impact of local variation in malaria transmission on the prevalence of SP-resistant haplotypes and selective sweep characteristics was investigated at an urban site with low parasite prevalence and two rural sites with moderate and high parasite prevalence. Methods Samples from three sites with different parasite prevalence were genotyped for resistance markers withinpfdhfr -ts andpfdhps and at microsatellites flanking these genes. Expected heterozygosity (He ) was estimated to evaluate genetic diversity. Results No difference in the prevalence of highly resistant DHFR 51I/59R/108N and DHPS 437G/540E was found between sites. Small differences in He flankingpfdhfr -ts andpfdhps were seen between rural-moderate and the other sites, as well as some shared haplotypes between the rural-high and urban-low sites. Conclusions The results do not show an effect of local variation in malaria transmission, as inferred from parasite prevalence, on SP-resistant haplotype prevalence.